Modulation of Hermetia illucens lipid profile by incorporation of an invasive macroalgae: a multigenerational approach - Louzado, Maria Fernandes (2022)
The world’s increasing demand for more sustainable food sources has brought more and more attention to aquaculture production in recent years. To overlap the dependence on pelagic fish and other plant-based options, insect meals are already being incorporated as alternative feed ingredient. However, the main source of polyunsaturated fatty acids (PUFA) in fish’s diets are still fish oil, obtained from overharvesting, mostly of pelagic fish, which competes directly with human consumption, and increasing the price of these ingredients and the need to find alternative solutions. Hermetia illucens, commonly known as black soldier fly, has a high protein content in the larval stage and the fatty acid content can be improved and modulated according to the substrate provided. In this work, it was incorporated the invasive macroalgae species Agarophyton vermiculophyllum, found widely in Ria de Aveiro, in the diet of H. illucens. The aim was to evaluate the bioconversion capacity of H. illucens and its ability to incorporate macroalgae PUFA in larval tissue when fed with diets with replacement levels of 25% and 50% of A. vermiculophyllum over four generations. Alongside, larvae grown parameters and conversion indexes were calculated and fatty acid profile was analysed by gas chromatography coupled to mass spectrometry (GC–MS). The results show the acceptability of the diet, since the larvae protein content was constant throughout the experience (38 to 46% of DM [dry matter]), independently of the substrate or generation. Mild deleterious effects were observed for 50% inclusion rate. The life cycle was slower in the first two generations, and the prepupal stage was reached earlier in the last two generations. In the diet formulation, the incorporation of 50% A. vermiculophyllum led to the occurrence of arachidonic (20:4) and docosahexaenoic acids (22:6). However, arachidonic acid was present in the larvae only in the third generation. A transgenerational decreased was observed in the saturated fatty acids content, defined mainly by the lauric acid content. An improvement in the PUFA content was reported, mostly due to linoleic acid abundance. Overall, the incorporation of A. vermiculophyllum in the diets of H. illucens larvae led to changes in its lipidic profile with increase in PUFA and reduction in saturated fatty acids. Larvae also demonstrated the ability to adapt to less suitable diets over several generations. Despite not being able to completely replace conventional n-3 PUFA sources in fish feed, black soldier fly larvae can be used as a protein source as well as other important fatty acids using an invasive macroalgae species as feeding substrate.